Neuromodulation of Persistent Activity and Working Memory Circuitry in Primate Prefrontal Cortex by Muscarinic Receptors - Vijayraghavan, Susheel; Everling, Stefan (Frontiers in Neural Circuits, 2021)
Neuromodulation by acetylcholine plays a vital role in shaping the physiology and functions of cerebral cortex. Cholinergic neuromodulation influences brain-state transitions, controls the gating of cortical sensory stimulus responses, and has been shown to influence the generation and maintenance of persistent activity in prefrontal cortex. Here we review our current understanding of the role of muscarinic cholinergic receptors in primate prefrontal cortex during its engagement in the performance of working memory tasks. We summarize the localization of muscarinic receptors in prefrontal cortex, review the effects of muscarinic neuromodulation on arousal, working memory and cognitive control tasks, and describe the effects of muscarinic M1 receptor stimulation and blockade on the generation and maintenance of persistent activity of prefrontal neurons encoding working memory representations. Recent studies describing the pharmacological effects of M1 receptors on prefrontal persistent activity demonstrate the heterogeneity of muscarinic actions and delineate unexpected modulatory effects discovered in primate prefrontal cortex when compared with studies in rodents. Understanding the underlying mechanisms by which muscarinic receptors regulate prefrontal cognitive control circuitry will inform the search of muscarinic-based therapeutic targets in the treatment of neuropsychiatric disorders.